Biomimetic artificial organelles with in vitro and in vivo activity triggered by reduction in microenvironment - T. Einfalt (Nature Portfolio, 2018)
The efficacy of stimuli-responsive enzyme delivery systems is usually limited to in vitro applications. Here the authors form artificial organelles by inserting stimuli-responsive protein gates in membranes of polymersomes loaded with enzymes and obtain a triggered functionality both in vitro and in vivo.